2017
DOI: 10.15740/has/ijps/12.2/309-313
|View full text |Cite
|
Sign up to set email alerts
|

Positive impact of abiotic stress on medicinal and aromatic plants

Abstract: SUMMARYAbiotic stress is the imbalance in the environmental status that affects the normal growth, development and reproduction of an organism. Various abiotic stresses are drought, salinity, heat, flood, reactive oxygen species etc. Generally stress cause reduction in quality and quantity of yield in agricultural crops. But in case of medicinal and aromatic plant it has been found to enhance both qualitative and quantitative yield. In this article we are going to understand the mechanism that will change our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In the same study the chlorophyll A content was reduced by 23.6% and 43.8% under 60 FC and 30% FC [23].The decrease in number of leaves per plant and leaf area observed in plants is a strategic adaptation manifested by plants to reduce water loss by transpiration. The physiological damage occurred in plants due to drought was evident by the degraded morphological characteristics of plant including plant height, number of leaves and SPAD value [24]. During the present study, the higher number of leaves (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…In the same study the chlorophyll A content was reduced by 23.6% and 43.8% under 60 FC and 30% FC [23].The decrease in number of leaves per plant and leaf area observed in plants is a strategic adaptation manifested by plants to reduce water loss by transpiration. The physiological damage occurred in plants due to drought was evident by the degraded morphological characteristics of plant including plant height, number of leaves and SPAD value [24]. During the present study, the higher number of leaves (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…Accumulation of phenylpropenoids and phenolic compounds were found higher during stress condition in plants [5,6]. The concentrations of various secondary plant products are strongly dependent on the growing conditions and physiology through altering the metabolic pathways responsible for the accumulation of the related natural products [4]. The expression levels of certain genes governing the production of such compounds have also been shown to be increased in response to various abiotic stresses [7].…”
Section: Introductionmentioning
confidence: 99%
“…Plants challenged with different types of abiotic and biotic stresses results into the reduction of different morphological characters such as height, leaf number, leaf area, number of branches, root volume, etc. [4] which ultimately leads to reduction of biomass production. There are different types of abiotic stress such as drought, low and high temperatures, salinity, alkalinity, ultraviolet radiation, ozone, metal ions, etc., which affect the metabolism of the plants.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental conditions and physiological processes in plants strongly impact the production of primary and secondary metabolites [8]. Under stress condition, secondary metabolite production increases to against abiotic and biotic stresses and directly reduce the quality and quantity in mostly crops [9], but it has been found in medicinal and aromatic plant vice versa [8]. This indicated that secondary metabolites positively respond in such plants more than protection and maintaining plants to survive in stressful environmental conditions.…”
Section: Introductionmentioning
confidence: 99%